Inventory of fruitfly species (Diptera: Tephritidae) on melon plants in Tanjung Seteko Village, Indralaya - Raja Bonar Lubis; Ajeng Tri Mughniy; Vera Fadhlia Amy; Nanda Wahyu Suryana; Muhari Muhari; Endi Darmawan; Chandra Irsan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Lubis RB, Mughniy AT, Amy VF, Suryana NW, Muhari M, Darmawan E, Irsan C. 2021. Inventory of fruitfly species (diptera: tephritidae) on melon plants in tanjung Seteko Village, Indralaya. In: Herlinda S et al. (Eds.), Prosiding Seminar NasionalLahan Suboptimalke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 878-883. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Inventory of fruitflies in Indonesia has been widely carried out, but inventory of fruitflies in melon plantations has never been carried out, while fruitfly attacks on melon plantations have the potential to harm fruit up to 30-60%. The purpose of this observation aimed to determine what kind of species are present in melon plantations in Tanjung Seteko Village, Indralaya and their populations. Observations were carried out on melon plantations in Tanjung Seteko Village using diagonal pattern sampling. Sampling using a modified Steiner trap placed at the sampling point horizontally and carried out for 3 days from 07.00 to 18.00 WIB. The results showed that the fruitfly species in melon plantations in Tanjung Seteko Village was Bactrocera carambolae. The results showed that the presence of Bactrocera cucurbitae, which is commonly found in melon plantations in many countries such as Pakistan, India, and Hawaii, was not found in melon plantations in Tanjung Seteko Village, Indralaya. The results of this observation indicate a decrease in the fly population for each sampling. The number of fruitfly population sampling on day 1 there were 324 fruitflies, on day 2 there were 242 fruitflies, and on day 3 there were 170 fruitflies. The conclusion from this observation is that Bactrocera carambolae is a species of fruitfly found in melon plantations in Tanjung Seteko Village and the average population is 245 fruitflies.